2019
DOI: 10.1002/csr.1832
|View full text |Cite
|
Sign up to set email alerts
|

Does involvement in corporate social irresponsibility affect the linguistic features of corporate social responsibility reports?

Abstract: Companies publish corporate social responsibility (CSR) reports to inform their stakeholders of their CSR efforts. However, the literature has shown that these reports can be used as a way to offset companies' involvement in corporate social irresponsibility (CSIR). By relying on a cognitive‐linguistic perspective, we investigate whether firms respond to their own irresponsible business conduct by changing their CSR reports' linguistic features and, if so, how. We use a sample of 135 large corporations headqua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 83 publications
(143 reference statements)
0
22
0
Order By: Relevance
“…As a result, they are more likely to contribute to the organization's goals through affective commitment (Bouraoui et al, 2019). On the other hand, employees are less committed to the company if their ethical convictions are at odds with the company's values (Corciolani et al, 2020). This view is also supported by Bizri et al (2021) in the Lebanese banking sector context, they found that organization's CSR activities have a highly significant and positive relationship with affective commitment.…”
Section: Csr and Affective Commitmentmentioning
confidence: 89%
“…As a result, they are more likely to contribute to the organization's goals through affective commitment (Bouraoui et al, 2019). On the other hand, employees are less committed to the company if their ethical convictions are at odds with the company's values (Corciolani et al, 2020). This view is also supported by Bizri et al (2021) in the Lebanese banking sector context, they found that organization's CSR activities have a highly significant and positive relationship with affective commitment.…”
Section: Csr and Affective Commitmentmentioning
confidence: 89%
“…For example, the United Nations global compact principles can be thought of as hypernorms which help to judge behaviors that are irresponsible (e.g., not respecting human rights, use of child labor, forced labor or slavery). Corciolani et al (2020) call for a universal framework that overcomes concerns about international differences in legal and cultural systems in an empirical study of 135 multinational firms defining irresponsibility through a firm’s involvement in human rights violations. Also, for Küberling-Jost (2019) irresponsible behavior is noncompliance with applicable laws and ethical standards, a behavior that violates generally accepted norms, standards and principles in society, and harms or disadvantages others and the environment.…”
Section: Csr and Csi: Blurred Lines And The Emergence Of Gray Zonesmentioning
confidence: 99%
“…On the contrary, socially irresponsible organization results in negative attitudes of the workforce. Employees also tend to be less committed to the organization if their ethical values conflict with the organization's values (Corciolani, Nieri, & Tuan, 2020). This suggests that employees' CSR perception influences their affective commitment toward the organization they are employed.…”
Section: Literature Reviewmentioning
confidence: 99%